Determining the Ideal Strategy and Modeling in Integrating Spending Reviews in Budget Decision Making at the Ministry of Health of the Republic of Indonesia - Beni Ruslandi; Bahrullah Akbar; Aries Djaenuri; Deti Mulyati (GoAcademica Research & Publishing, 2020)
This study aims to find the right strategy and modelling in integrating Spending Review in budget decision making at the Ministry of Health of the Republic of Indonesia. This study uses a qualitative approach with an exploratory method, in which the researcher seeks to explore and build the phenomena being studied to answer the previously formulated problems. The results showed that the spending review integration strategy was divided into three dimensions, namely the organizational size, the process dimension and the time dimension. Meanwhile, the modelling used in integrating spending review in budget decision making in the Indonesian Ministry is known as the Comprehensive Monitoring and Evaluation Model for Budget Management Ministries / Institutions.